Odkrycie grobu Filipa Macedońskiego w Verginie - Gawłowska, Wanda (Acta Universitatis Lodziensis. Folia Archaeologica, 1990)
The paper discusses the discovery of the tomb of Philip of Macedonia in 1977. This grave discovered by Manolis Andronikos, the professor of University of Salonika, belonged to the royal family (as it is indicated by the inventory of the grave). Some of these objects because of their specific character are inevitably associated with Philip II. All objects found during excavations were sent to the Museum in Salonika.